2019
DOI: 10.1002/jbmr.3890
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid Improves Muscle Function in Healthy Mice Treated with Chemotherapy

Abstract: Carboplatin is a chemotherapy drug used to treat solid tumors but also causes bone loss and muscle atrophy and weakness. Bone loss contributes to muscle weakness through bone-muscle crosstalk, which is prevented with the bisphosphonate zoledronic acid (ZA). We treated mice with carboplatin in the presence or absence of ZA to assess the impact of bone resorption on muscle. Carboplatin caused loss of body weight, muscle mass, and bone mass, and also led to muscle weakness as early as 7 days after treatment. Mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 75 publications
(140 reference statements)
1
37
0
Order By: Relevance
“…Though the goal of the study to examine cachexia in a context of CRC LM was achieved, future studies may consider using lower doses of C26 tumor cells or perhaps other CRC cells that may allow the progression of cachexia to extend beyond 2 weeks. Moreover, in the present study, we did not take into consideration whether the administration of chemotherapeutics further aggravate muscle wasting, especially considering that our lab and others have demonstrated that several anticancer compounds induce cachexia independently of their effects on tumor growth (24,26,27,29,30,60). Lastly, another limitation of the current study was the focus on male animals, leaving out possible sex differences in response to LMs.…”
Section: Discussionmentioning
confidence: 92%
“…Though the goal of the study to examine cachexia in a context of CRC LM was achieved, future studies may consider using lower doses of C26 tumor cells or perhaps other CRC cells that may allow the progression of cachexia to extend beyond 2 weeks. Moreover, in the present study, we did not take into consideration whether the administration of chemotherapeutics further aggravate muscle wasting, especially considering that our lab and others have demonstrated that several anticancer compounds induce cachexia independently of their effects on tumor growth (24,26,27,29,30,60). Lastly, another limitation of the current study was the focus on male animals, leaving out possible sex differences in response to LMs.…”
Section: Discussionmentioning
confidence: 92%
“…antiresorptive treatments) preserve bone and muscle mass in the presence of platinum-based chemotherapies. 70,71 Additionally, we have previously indicated that use of ACVR2B/Fc preserves muscle and bone in the presence of the commonly used chemotherapy regimen Folfiri. 22 However, to our knowledge, this is the first time that ACVR2B/Fc has shown to preserve bone and muscle together in a model of metastatic CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is of particular importance as we and others have demonstrated that several chemotherapies induce multi-organ cachexia independent of their effects on tumour growth. 22,23,71,[91][92][93] In this regard, targeting ACVR2B in combination with chemotherapy may prove to be a viable approach in minimizing tumour progression and the multi-organ perturbations that occur with the progression of cancer cachexia. Moreover, the present study only examined the benefits of ACVR2B/Fc on male mice bearing HCT116 LM, and as sexual dimorphism has been observed in the progression of cachexia in CRC, future studies should investigate whether ACVR2B/Fc benefits equally span across both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Protein lysates from gastrocnemius or RF muscles were prepared as previously described using NP‐40 lysis buffer (50 mM Tris pH 8.0, 150 mM NaCl, 1% NP‐40), cOmplete Mini EDTA‐free protease inhibitor tablet (MilliporeSigma, Burlington, MA, USA), phosphatase inhibitors (1 mM Na 3 OV 4 , 5 mM NaF, 1 mM phenylmethylsulfonyl fluoride) and PhosSTOP phosphatase inhibitor tablet (Sigma‐Aldrich, St Louis, MO, USA) (Hain et al., 2020). Protein concentration was determined by bicinchoninic acid assay (BCA) protein assay, Thermo Fisher, Waltham, MA, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Cachexia can exist as a spectrum from muscle weakness with mild weight loss to profound muscle weakness and wasting (Fearon et al., 2011). There are no current treatments for cancer cachexia and some cancer treatments have been shown to also cause cachexia (Barreto et al., 2016; Coletti, 2018; Damrauer et al., 2018; Hain et al., 2019, 2020; Martin et al., 2015).…”
Section: Introductionmentioning
confidence: 99%